ETNOMATEMATIKA KARYA SENI BATIK KHAS SUKU OSING BANYUWANGI SEBAGAI BAHAN LEMBAR KERJA SISWA MATERI GEOMETRI TRANSFORMASI - Khofifah, Lita; Sugiarti, Titik; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2018)
Ethnomatematics is a mathematical consept contained in everyday life activities that have been entrenched. This research was condusted at Umah Batik Sayu Wiwit which is located at Jl. Sayuwiwit, Temanggungan, Kampung melayu, Banyuwangi. This study aims to describe ethnomatematics in batik artwork the typical Osing tribe of Banyuwangi on the concept of transformation geometry and make it as student’s worksheet theme. this type of research is qualitative research with ethnographic research. the collection method in this study was observed by 3 observers, interviews with 3 batik makers and documentation. The object of this research is Gajah oling motive, Kangkung Setingkes motive, Gedegan motive, Kopi Pecah motive, Sembruk Cacing motive and Paras Gempal motive. The results of data evaluation were analyzed descriptively. The results of this study prove the reflection consepts, translation concepts, rotation concepts and dilation concepts. Keyword : Ethnomatematics, Batik Artwork, Transformation Geometry.